2011
DOI: 10.1186/1471-2458-11-869
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition among HIV-positive children in Dar es Salaam, Tanzania: antiretroviral therapy alone is not enough

Abstract: BackgroundThe prevalence of HIV/AIDS has exacerbated the impact of childhood undernutrition in many developing countries, including Tanzania. Even with the provision of antiretroviral therapy, undernutrition among HIV-positive children remains a serious problem. Most studies to examine risk factors for undernutrition have been limited to the general population and ART-naive HIV-positive children, making it difficult to generalize findings to ART-treated HIV-positive children. The objectives of this study were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
90
3
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(110 citation statements)
references
References 32 publications
(55 reference statements)
15
90
3
2
Order By: Relevance
“…Like in other studies conducted in similar settings among HIV-positive children [9,10], adults were more likely to succumb to undernutrition when they had poor feeding practices such as consuming foods with low dietary diversity. Moreover, only a small proportion consumed protein-rich foods, fruits, or vegetables in their routine meals, similar to other studies [18][19][20].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Like in other studies conducted in similar settings among HIV-positive children [9,10], adults were more likely to succumb to undernutrition when they had poor feeding practices such as consuming foods with low dietary diversity. Moreover, only a small proportion consumed protein-rich foods, fruits, or vegetables in their routine meals, similar to other studies [18][19][20].…”
Section: Discussionmentioning
confidence: 52%
“…Such unprecedented magnitude of undernutrition is not uncommon in this [9,11] and other areas with similar context [12]. A syndemic theory can help explain such high magnitude of undernutrition in this context.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The HFIAS has been used in several HIV cohorts in the US [47,48], and among HIV-positive populations in Zambia, Uganda and Kenya [49][50][51]. The Household Food Security Scale-Short Form (HFSS-SF) was recently applied in cohorts of PLHIV in Tanzania [52] and Vietnam [53].…”
Section: Food and Nutrition Scurity Measuresmentioning
confidence: 99%
“…However, Magadi 5 reported that the risk of malnutrition was particularly high among infants aged 1 year whose mothers were HIV positive. Another study suggested that one of the factors associated with underweight and wasting was feeding frequency among ART treated HIV positive children below 2 years old 6 . Therefore, several factors may contribute to 2014;80 4 :199 207 Original Article…”
Section: Introductionmentioning
confidence: 99%